(untitled) (Research, Society and Development, 2021)
In the meat and milk of ruminants, the profile of fatty acids (FA) is differentiated by the higher content of conjugated linoleic acid (CLA), a molecule with bioactive properties. The present work was carried out by bibliographical search with the objective of describing the BH process with its main routes and describing the main effects of lipid supplementation on the FA profile of ruminant meat, highlighting the potential effects of medium chain FA (MCFA). The ruminal biohydrogenation (BH) process is responsible for the synthesis of CLA, and the manipulation of this process is the focus of many research attempting to increase the beneficial FA in ruminant products. By inhibiting ruminal BH, there is an increase the CLA content being absorbed by the duodenum. For this purpose, the use of unsaturated FA and MCFA sources has been studied. However, there is little research on the effect of MCFA in BH. These FA have the potential to increase the fluidity of gram-positive bacterial membranes, making them inefficient, decreasing their activity, which causes a reduction in the second stage of BH and, as a consequence, an accumulation of CLA in the rumen. As main sources of MCFA, only coconut oil, palm oil and licuri stand out. Further research is needed to understand how they are compared to other methods of ruminal manipulation and efficiency to improve the quality of ruminant products for human consumption, focusing on the FA profile.